Wittgenstein and the justification of hinge propositions - Gómez Alonso, Modesto Manuel (Estudios de Filosofía, 2019)
Questions about the possibility of thought as an activity directed to reality, are deeper than those concerning the possibility of knowledge. These deeper questions have found intuitive expression in the Agrippan Trilemma, particularly in the trope of arbitrary presupposition. This trope can be raised as a criticism of current varieties of hinge epistemology inspired by Wittgenstein, mainly by virtue of the fact that Wittgensteinian hinges are foundational principles governing our epistemic practice. As such, they are necessarily unsupportable, being thus dificult to see how it would be possible to conciliate the hinges’ lack of support with their being not bare, arbitrary assertions. Facing up to this challenge, hinge epistemologists have proposed practical —though not pragmatic— arguments according to which hinges are either postulates legitimately demanded to every epistemic agent or rules constitutive of quotidian practices. It is the aim of this article to show that practical arguments for hinges fall short, necessarily so.